ANALISIS NILAI TAMBAH MAGGOT SEBAGAI PROSPEK BISNIS BERKELANJUTAN DI PULAU LOMBOK - Novida, Sari; Sulastri, Meilinda Pahriana (Program Studi Agribisnis Fakultas Pertanian, 2025)
NTB is one of the provinces that is seriously handling and processing organic and inorganic waste, this is in line with the government's â€œZero Wasteâ€ program, one of which uses maggot from the Black Soldier fly (BSF) species. Maggot cultivation in the research area uses 60% of organic waste from expired food and 40% of wet organic waste from households and markets. Maggot can be used as feed for fish and poultry, as organic fertilizer and as raw material for cosmetics. The research objectives are: (1) Analyzing the added value produced by fresh maggot, dried maggot, solid kasgot and liquid kasgot on Lombok Island, (2) Analyzing business opportunities for fresh maggot, dried maggot, solid kasgot and liquid kasgot on Lombok Island, (3) Analyzing the most potential maggot products to be developed on the island of Lombok. The method in this research is descriptive quantitative and qualitative with the approach of value-added analysis and SWOT analysis. Based on the results of the research, the average maggot business actor comes from the environmental care community. There are several products produced and can be commercialized from maggot cultivation, including: maggot eggs, baby maggot, adult maggot, pupae, organic fertilizer (solid kasgot) and liquid kasgot. Maggot cultivation is integrated by business actors with poultry farming, freshwater fish and food and horticultural crop cultivation. The added value generated from maggot cultivation is IDR 1,010,589 per month and IDR 12,127,068 per year. Maggot cultivation activities are analyzed using SWOT analysis with the IFAS and EFAS approaches to see its prospects in the future. Currently, maggot cultivation is in quadrant III, which means that this business has internal weaknesses and faces external threats. To overcome its weaknesses, product innovation is needed to generate added value, such as switching to derivative products to make maggot flour and maggot oil, the active role of the government in regulations related to maggot and the availability of feed, as well as seeking access to export markets, and motivation for human resources.